2018
DOI: 10.1002/jaoc.12037
|View full text |Cite
|
Sign up to set email alerts
|

Individuals With Visual Disabilities and Substance Use Disorders: Recommendations for Counselors

Abstract: Given the prevalence of substance use disorders in individuals with visual disabilities, counselors must be prepared to address the distinctive needs of this population. The authors summarize evidence‐based interventions, offer contextual considerations, and provide recommendations for counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…While previous research is limited, studies suggest that substance use disorders may be elevated among people with vision impairment, and have posited that alcohol may be used to self-medicate or cope. 32-34 Previous research has also found that adults with TBI are at increased risk for binge drinking, 35 a population likely represented in the cognitive disabilities subgroup in our study. Additional understanding of what disability subgroups are particularly vulnerable to excessive drinking would improve our ability to engage in targeted assessment and intervention efforts.…”
Section: Discussionsupporting
confidence: 50%
“…While previous research is limited, studies suggest that substance use disorders may be elevated among people with vision impairment, and have posited that alcohol may be used to self-medicate or cope. 32-34 Previous research has also found that adults with TBI are at increased risk for binge drinking, 35 a population likely represented in the cognitive disabilities subgroup in our study. Additional understanding of what disability subgroups are particularly vulnerable to excessive drinking would improve our ability to engage in targeted assessment and intervention efforts.…”
Section: Discussionsupporting
confidence: 50%
“…Some articles identified by the primary theme of Cybernetics directly reference the intersection of various forces as creating the interaction effect, such as with family of origin and career impact (Barclay et al, 2011; Dipeolu et al, 2020; Fider et al, 2014; Johnson et al, 2014; Lustig & Xu, 2018; Maddy et al, 2015; Makhija et al, 2019; McAdams et al, 2018; Porter & Henriksen, 2016; Waliski et al, 2012; Wright et al, 2020), family of origin and symptom development and treatment (Buser et al, 2014; Haiyasoso & Trepal, 2019; Lampis et al, 2020; Noble & Bradley, 2019; Noble et al, 2017; Wang et al, 2016; Watts et al, 2020; Williams et al, 2016), familial dynamics and spiritual development (Hooper & Newman, 2011; Jankowski & Hooper, 2014; Muselman & Wiggins, 2012), familial dynamics and developmental outcomes (Fish & Priest, 2011; Gold, 2013; He, 2017; Hoekstra & Katz, 2021; Kataoka & Tsuchiya, 2020; Lenz & Oliver, 2018; Li et al, 2018; Messina et al, 2018; Wilkinson & Dewell, 2019), and attachment development and impact (Bernardon & Pernice-Duca, 2012; Coffman & Swank, 2021; Myrick et al, 2014; Toof et al, 2020; Willcox et al, 2019). Others allude to cybernetics indirectly such as with physical disability and substance abuse (Feather et al, 2018), as well as other contextual factors like incarceration (Tadros, 2021; Tadros & Finney, 2018). The articles with this designation heuristic were further identified by two secondary themes: disorders and development.…”
Section: Resultsmentioning
confidence: 99%
“…Articles included in the disorders secondary theme recommend that our conceptualization of a disorder in the identified client or family recognize and incorporate a cybernetic etymology, development and maintenance of the identified disorder. Articles consistent with this secondary theme applied this cybernetic awareness to issues in couples and family systems work (Asfaw et al, 2020), addiction related disorders (Barringer & Papp, 2020; Belmontes, 2018; Day, 2017; Jankowski & Hooper, 2014), trauma and grief related disorders (Dickens, 2014; Katafiasz, 2020; Muselman & Wiggins, 2012; Overton & Cottone, 2016; Southern & Sullivan, 2021), self-harm and suicidality (Buser et al, 2014), physical disabilities, somatoform disorders, and illness (Feather et al, 2018; Sperry, 2012; Taylor & Lewis, 2018), and nonspecific pathology (Hooper & Newman, 2011; Zagefka et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Given the significant percentage of the population of people with disabilities, it is almost inevitable that counselors from all branches of the profession will continually encounter individuals with disabilities throughout their careers (Chapin et al., 2018; Feather et al., 2018; Smart, 2018). Suppose counselor education programs are critical to the transformation of the profession.…”
Section: Discussionmentioning
confidence: 99%